# Solve for x 7x+14/3-17-(3x)/5=6x-4x+23-5

7x+143-17-3×5=6x-4x+23-5
Simplify 7x+143-17-3×5.
To write 7x as a fraction with a common denominator, multiply by 55.
7x⋅55-3×5+143-17=6x-4x+23-5
Combine 7x and 55.
7x⋅55-3×5+143-17=6x-4x+23-5
Combine the numerators over the common denominator.
7x⋅5-3×5+143-17=6x-4x+23-5
Find the common denominator.
Multiply 7x⋅5-3×5 by 33.
7x⋅5-3×5⋅33+143-17=6x-4x+23-5
Combine.
(7x⋅5-3x)⋅35⋅3+143-17=6x-4x+23-5
Multiply 143 by 55.
(7x⋅5-3x)⋅35⋅3+143⋅55-17=6x-4x+23-5
Combine.
(7x⋅5-3x)⋅35⋅3+14⋅53⋅5-17=6x-4x+23-5
Write -17 as a fraction with denominator 1.
(7x⋅5-3x)⋅35⋅3+14⋅53⋅5+-171=6x-4x+23-5
Multiply -171 by 1515.
(7x⋅5-3x)⋅35⋅3+14⋅53⋅5+-171⋅1515=6x-4x+23-5
Multiply -171 and 1515.
(7x⋅5-3x)⋅35⋅3+14⋅53⋅5+-17⋅1515=6x-4x+23-5
Reorder the factors of 5⋅3.
(7x⋅5-3x)⋅33⋅5+14⋅53⋅5+-17⋅1515=6x-4x+23-5
Multiply 3 by 5.
(7x⋅5-3x)⋅315+14⋅53⋅5+-17⋅1515=6x-4x+23-5
Multiply 3 by 5.
(7x⋅5-3x)⋅315+14⋅515+-17⋅1515=6x-4x+23-5
(7x⋅5-3x)⋅315+14⋅515+-17⋅1515=6x-4x+23-5
Combine fractions with similar denominators.
(7x⋅5-3x)⋅3+14⋅5-17⋅1515=6x-4x+23-5
Simplify the expression.
Multiply 14 by 5.
(7x⋅5-3x)⋅3+70-17⋅1515=6x-4x+23-5
Multiply -17 by 15.
(7x⋅5-3x)⋅3+70-25515=6x-4x+23-5
Subtract 255 from 70.
(7x⋅5-3x)⋅3-18515=6x-4x+23-5
Multiply 5 by 7.
(35x-3x)⋅3-18515=6x-4x+23-5
(35x-3x)⋅3-18515=6x-4x+23-5
Subtract 3x from 35x.
32x⋅3-18515=6x-4x+23-5
Simplify the expression.
Multiply 3 by 32.
96x-18515=6x-4x+23-5
Split the fraction into multiple fractions.
96×15-18515=6x-4x+23-5
96×15-18515=6x-4x+23-5
Reduce the expression 96×15 by cancelling the common factors.
Factor 3 out of 96x.
3(32x)15-18515=6x-4x+23-5
Factor 3 out of 15.
3(32x)3(5)-18515=6x-4x+23-5
Cancel the common factor.
3(32x)3⋅5-18515=6x-4x+23-5
Rewrite the expression.
32×5-18515=6x-4x+23-5
32×5-18515=6x-4x+23-5
Reduce the expression 18515 by cancelling the common factors.
Factor 5 out of 185.
32×5-5(37)15=6x-4x+23-5
Factor 5 out of 15.
32×5-5⋅375⋅3=6x-4x+23-5
Cancel the common factor.
32×5-5⋅375⋅3=6x-4x+23-5
Rewrite the expression.
32×5-373=6x-4x+23-5
32×5-373=6x-4x+23-5
32×5-373=6x-4x+23-5
Simplify 6x-4x+23-5.
Subtract 4x from 6x.
32×5-373=2x+23-5
Subtract 5 from 23.
32×5-373=2x+18
32×5-373=2x+18
Move all terms containing x to the left side of the equation.
Subtract 2x from both sides of the equation.
32×5-373-2x=18
To write -2x as a fraction with a common denominator, multiply by 55.
32×5-2x⋅55-373=18
Combine -2x and 55.
32×5+-2x⋅55-373=18
Combine the numerators over the common denominator.
32x-2x⋅55-373=18
Simplify each term.
Simplify the numerator.
Factor 2x out of 32x-2x⋅5.
Factor 2x out of 32x.
2x(16)-2x⋅55-373=18
Factor 2x out of -2x⋅5.
2x(16)+2x(-1⋅5)5-373=18
Factor 2x out of 2x(16)+2x(-1⋅5).
2x(16-1⋅5)5-373=18
2x(16-1⋅5)5-373=18
Multiply -1 by 5.
2x(16-5)5-373=18
Subtract 5 from 16.
2x⋅115-373=18
2x⋅115-373=18
Multiply 11 by 2.
22×5-373=18
22×5-373=18
22×5-373=18
Move all terms not containing x to the right side of the equation.
Add 373 to both sides of the equation.
22×5=18+373
To write 18 as a fraction with a common denominator, multiply by 33.
22×5=18⋅33+373
Combine 18 and 33.
22×5=18⋅33+373
Combine the numerators over the common denominator.
22×5=18⋅3+373
Simplify the numerator.
Multiply 18 by 3.
22×5=54+373
22×5=913
22×5=913
22×5=913
Multiply both sides of the equation by 522.
522⋅22×5=522⋅913
Simplify both sides of the equation.
Simplify 522⋅22×5.
Cancel the common factor of 5.
Cancel the common factor.
522⋅22×5=522⋅913
Rewrite the expression.
122⋅(22x)=522⋅913
122⋅(22x)=522⋅913
Cancel the common factor of 22.
Factor 22 out of 22x.
122⋅(22(x))=522⋅913
Cancel the common factor.
122⋅(22x)=522⋅913
Rewrite the expression.
x=522⋅913
x=522⋅913
x=522⋅913
Multiply 522⋅913.
Multiply 522 and 913.
x=5⋅9122⋅3
Multiply 5 by 91.
x=45522⋅3
Multiply 22 by 3.
x=45566
x=45566
x=45566
The result can be shown in multiple forms.
Exact Form:
x=45566
Decimal Form:
x=6.893‾
Mixed Number Form:
x=65966
Solve for x 7x+14/3-17-(3x)/5=6x-4x+23-5